The impact of a student-developed, student-marketed, student-implemented and student-led 8-week health and wellness program on faculty and staff participation consistency - Allen, Jeffrey; Olomofe, Charles; Lehman, Shane (Frontiers in Public Health, 2025)
College and university faculty and staff in the United States experience diabetes rates higher than the national average, elevated cholesterol levels, receive fewer than the recommended 7 h of sleep per night, and routinely experience overwhelming anxiety. In response, some universities have implemented top-down approaches to employee wellness but there is scant evidence of student-driven approaches to faculty and staff wellness. The current study examines improvement in faculty and staff participation consistency when enrolled in a fully student-developed, −implemented, and -evaluated 8-week health and wellness program. The 78 participants in the study were asked to complete both a pre- and post-intervention Likert scale questionnaire, which was assessed by independent T-tests. There was a statistically significant difference in mean of the participation of staff in the wellness program activities within the university and at local community activities pre- and post-challenge (Mean difference: −0.456, 95% CI: −0.882 – −0.048; p = 0.029). In a similar vein, there was a statistically significant difference between pre-intervention and post-intervention participation in nutritional programs at the university and the surrounding local community by staff and faculty (Mean difference: −0.472, 95% CI: −0.817 – −0.127; p = 0.008). This increased participation could be the result of nudging used throughout the intervention, which included weekly consistency reporting reminders, weekly newsletters, regular email promotions, mailbox stuffers, and personal reminders to participate. It is our belief that this nudging approach led to habituation of participation amongst faculty and staff members.